LINTASAN SEJARAH INDONESIA DALAM NOVEL-NOVEL SUPARTO BRATA - Sungkowati, Yulitin (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2009)
This writing is aimed to discuss about Indonesian history that is described and interpreted by Suparto Brata in his novels, written in Indonesian and Javanese, mainly Sala Lelimengan (1965), Surabaya Tumpah Darahku (1978), November Merah (1984), Kremil (2002), Saksi Mata (2002), Donyane Wong Culika (2004), Gadis Tangsi (2004), Mencari Sarang Angin (2005), Kerajaan Raminem (2005), Dom Sumurup ing Banyu (2006), and Mahligai di Ufuk Timur (2007). The course of Indonesian history in the novels ranges from Dutch colonialism era up to new sociopolitical order era. If the formal history records famous person only (usually men only), the history of Suparto Brata’s version presents the role and struggle of people from various social class, profession, gender, age, and the victims of Indonesian regime all with its humanistic perspective. Indonesian history is interpreted as the struggle against stupidity and betrayal of people who didn’t learn from the past. The choice of using historical subject can be read and interpreted as an effort of the writer to question and ask readers to understand and appreciate the history of their nation as a meaningful thing, a valuable lesson for a better future.